Creep behavior of a precipitation-strengthened A2-B2 refractory high entropy alloy - Yang, Liu; Sen, Sandipan; Schliephake, Daniel; Vikram, R․ J․; Laube, Stephan; Pramanik, Aparajita; Chauhan, Ankur; Neumeier, Steffen; Heilmaier, Martin; Kauffmann, Alexander (Acta Materialia, 2025)
Refractory compositionally complex alloys consisting of a disordered A2 matrix and ordered B2 precipitates mimic the microstructures of state-of-the-art, Ni-based superalloys with A1 matrix and L12 precipitates. The former are promising candidates for high-temperature applications because of their high melting points. 27.3Ta-27.3Mo-27.3Ti-8Cr-10Al (in at. %, TMT-8Cr-10Al) is a relevant example where this A2-B2, two-phase microstructure is formed by a precipitation reaction and remains stable even at temperatures close to the precipitate solvus temperature (TS). The present study systematically addresses the creep response of polycrystalline TMT-8Cr-10Al at temperatures of 1000 °C and above. Compared to polycrystalline, single-phase A2 and B2 high entropy alloys, a substantially higher compression creep resistance is observed for the two-phase alloy while minimum creep rates comparable to those of state-of-the-art single-crystalline A1-L12 CMSX-4 are found. This is specifically remarkable considering the polycrystalline condition of TMT-8Cr-10Al, the open matrix A2 crystal structure and the close proximity of the test temperatures to the solvus temperature with 0.98 TS compared to 0.85 TS for CMSX-4. Consistent with a positive lattice misfit, directional coarsening of precipitates in TMT-8Cr-10Al is noted to be perpendicular to the compression direction after creep in grains with 〈100〉 close to the compression direction.
CRIS-Team Scopus Importer:2025-02-28
Keywords: Compositionally complex alloys; Creep; High temperature; Refractory high entropy alloys; Super alloys